KOSMOPOLITANISME SEBAGAI JALAN KELUAR ATAS TEGANGAN ABADI ANTARA NEOKOLONIALISME, RADIKALISME AGAMA, DAN MULTIKULTURALISME | COSMOPOLITANISM AS A SOLUTION TO THE ETERNAL TENSION BETWEEN NEO-COLONIALISM, RELIGIOUS RADICALISM, AND MULTICULTURALISM - Reza A.A Wattimena (Jurnal Ledalero, 2018)
Abstract: This writing offers allternative point of view on the debate between universalism and particularism. This debate becomes the tension between neocolonialism, multiculturalism and religious radicalism in 21st century. The method of the writing is critical textual analysis with clear definitions of universalism, particularism, multiculturalism and religious radicalism, and then cosmopolitanism as an alternative point of view. As a conceptual approach, cosmopolitanism has impacts in various areas of life. This impact will also be elaborated in this writing. Key Words: Universalism, Particularism, Neocolonialism, Religious Radicalism, Multiculturalism, Cosmopolitanism. Abstrak: Tulisan ini hendak mengajukan jalan keluar teoretis untuk perdebatan universalisme dan partikularisme. Perdebatan ini berkembang menjadi tegangan antara neokolonialisme, multikulturalisme dan radikalisme agama di abad XXI. Metode yang digunakan adalah analisis tekstual kritis dengan terlebih dahulu memberikan definisi tentang universalisme, partikularisme, multikulturalisme, dan radikalisme agama. Artikel berakhir dengan jalan keluar yang diajukan, yakni kosmopolitanisme. Sebagai sebuah pendekatan, kosmopolitanisme juga memiliki dampak luas di berbagai bidang. Dampak ini juga akan menjadi bagian dari tulisan. Kata-kata Kunci: Universalisme, Partikularisme, Neokolonialisme, Radikalisme Agama, Multikulturalisme, Kosmopolitanisme.